Fructose uptake and influence on growth of and nitrogen fixation by Anabaena variabilis. - Haury, J F (1981)
Fructose is specifically taken up by nitrogen-fixing cultures of Anabaena variabilis in the light and lowers the doubling time from 24 to 8 h. The kinetics for both fructose-dependent growth and fructose uptake are exponential. The apparent Km for fructose uptake in N2-fixing cultures is 160 microM for cells not previously exposed to fructose and 50 microM in cells adapted to fructose. Picomolar amounts of [14C]fructose are scavenged from the medium and accumulate in filaments. Heterocysts of fructose-adapted filaments accumulate 14C from fructose within 20 min. Short-term experiments with fructose-starved cultures provide evidence that nitrogenase activity, protein, and chlorophyll content change within one generation time upon addition of fructose. In long-term experiments, the amount of fructose initially present in the medium determines heterocyst number and packed-cell volume. Photosynthetic oxygen evolution and amounts of chlorophyll decrease with exogenous fructose concentrations greater than 20 mM.